The burden of coronary revascularization associated with lipoprotein(a) in patients with atherosclerotic cardiovascular disease: data from the UK Biobank. (3rd October 2022) - Welsh, P; Byrne, H; Costa-Scharplatz, M; Fonseca, A F; Itani, T; Farries, G; Zabiby, A A; Narasimham, S; Martin, L; Sattar, N
Abstract: Background/Introduction: Elevated lipoprotein(a) [Lp(a)] is an inherited, independent, and causal risk factor for atherosclerotic cardiovascular disease (ASCVD). In a previous analysis of 30, 510 ASCVD patients from UK Biobank, adjusted models showed a 100 nmol/L (≈50 mg/dL) difference in Lp(a) was associated with a 19% (95% CI 14–23%) higher risk of coronary revascularization (Welsh P, 2022). Purpose: To determine the absolute risk for coronary revascularization in an ASCVD population with elevated versus normal Lp(a) levels. Methods: This was an observational, retrospective study including 32, 537 patients from UK Biobank with an ASCVD diagnosis (CHD, cerebrovascular or peripheral arterial disease). Absolute risk (AR) of coronary revascularization (number of coronary revascularizations per 100-person-years) was reported in patients with normal (<65 nmol/L ≈ 30 mg/dL; n=22, 257) and elevated (≥150 nmol/L ≈ 70 mg/dL; n=5, 204) Lp(a) levels across two time periods: within the first year of ASCVD diagnosis, and using all available follow-up data (median 4.7 years). Lp(a) was measured in an accredited single laboratory using a method standardized to WHO/IFCC reference material. The AR was also calculated for various subgroups within the ASCVD population. Results: Within the first year after ASCVD diagnosis, 628 (12.07%) of the population with elevated Lp(a) underwent coronary revascularization compared to 1, 787 (8.03%) with normal Lp(a). Those with elevated Lp(a) had a higher AR (14.00 per 100-person-years, 95% CI 13.02–14.99; p<0.001) than those with normal Lp(a) (9.34; 95% CI 8.92–9.76). This also held in a subgroup with myocardial infarction (MI; n=9, 588), AR of 18.98 (95% CI 16.95–21.01) in those with elevated Lp(a) (n=1, 571) vs. AR of 13.02 (95% CI 12.16–13.89) in those with normal Lp(a) (n=6, 441) (p<0.001). AR of coronary revascularization within the first year of ASCVD diagnosis was also greater in participants with family history of CV disease (p<0.001) and premature CV disease (<60 years of age) (p<0.001). When using all available follow-up, AR of coronary revascularization was higher in participants with elevated versus normal Lp(a) in the ASCVD population (3.79 vs 2.55; p<0.001) and across all subgroups. Conclusion: Elevated Lp(a) in patients with ASCVD was associated with increased risk of coronary revascularization in the first year (and subsequently), including those with a prior MI, premature CV disease, or family history of CV disease. Lp(a) testing in ASCVD patients can therefore aid estimations for the risk of revascularization, and thus the targeting of additional therapies to lower such risks. Funding Acknowledgement: Type of funding sources: None.